Elastic and radiation shielding properties of zinc borotellurite glass systems: The impact of gadolinium oxide - Nazrin S.N.; Amat A.; Issa S.A.M.; Zakaly H.M.H.; Gunasekaran S.S.; Zaman H.B.; Zaid M.H.M.; Tahir M.H.M.; Shaaban I.A.; Sharma I. (Elsevier B.V., 2025)
Using the formula [(TeO2)70(B2O3)30], this study examines the impact of Gd2O3 on the elasticity and radiation shielding characteristics of zinc borotellurite glass. Glass samples containing 1?5% mol% Gd2O3 were created by employing the melt quench technique. XRD verified that they are amorphous in nature, and the existence of TeO3, TeO4, BO3, and BO4 vibrational groups was revealed by infrared spectra. The structural alterations were shown by the range of longitudinal and shear ultrasonic velocities, which were 3908?4076 m/s and 2222?2277 m/s, respectively. The glass's rigidity was improved by the large rise in elastic moduli, such as bulk (45 GPa), longitudinal (80 GPa), shear (25 GPa), and Young's moduli (60 GPa), with a higher Gd2O3 content. Higher concentrations of Gd2O3 resulted in a rise in the mass attenuation coefficient (??), as measured by WinXcom, which enhanced gamma-ray shielding. The half-value layer (HVL) and mean free path (MFP) at 0.662 MeV decreased with increasing Gd2O3 in a consistent manner. The maximum density and optimum gamma-ray shielding performance were found in the glass containing 5 mol% Gd2O3. These results show Gd2O3 for applications needing greater rigidity and better radiation protection by demonstrating how it affects the elastic and radiation-shielding efficiency of the glass network. ? 2024 Elsevier B.V.